The Role of the Sabhara Unit Patrol Unit in Preventing Student Brawls in Cirebon Police Jurisdiction: Peran Unit Patroli Satuan Sabhara dalam Mencegah Tawuran Antar Pelajar di Wilayah Hukum Polres Cirebon Kota - Prawira, Muhammad Dito (Akademi Kepolisian Republik Indonesia, 2021)
This research is motivated by the high cases of student brawl at Polres Cirebon Kota. Police prevention efforts are needed in the form of police patrols. This study aimed to describe and analyze how the implementation of the role of patrols, factors that influence the role of patrols in preventing student brawl, and efforts made by Sabhara Polres Cirebon Kota in carrying out patrols. This research uses role theory, management theory, and patrol concepts. The study was conducted with a qualitative approach. Data sources include primary and secondary data. Data collection techniques used are through interviews, observation and document review. The analysis used data reduction, data presentation and conclusion drawing. The results of the study found that the implementation of the role of patrols was still not optimal, there were factors that influenced it, the lack of personnel and training, not in accordance with the regulations on patrols and SOPs for patrols, the Polres Cirebon Kota jurisdiction. Efforts made to optimize patrols are conditions of patrols, improved police activities, patrols in areas and vulnerable times. Suggestions from researchers to optimize the implementation of patrol is to provide reward and punishment to patrol members so that the implementation of patrols achieves the expected results and objectives, Bag Sumda provides training and vocational education to patrol members to improve their abilities. The Saturday Sambang Ciko program is reviewed and evaluated so that in the future it will be an appropriate effort for the Polres Cirebon Kota Station to prevent student brawls.